DESIGNING A DOMESTIC MOBILE APPS: SAVIOR - T. Zalizam T. Muda; Wong Xin Yi; Teh Xiao Lin, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The paper attempts to describe about designing and developing an android-based mobile application for home services. The application focuses on clients and service providers. The clients who are the target audiences while the service providers are the workers that can give the services locally. The main objective of this development is to create a mobile application called Savior. The first part of the tasks concerned on the analysis and design phases which include interface design, navigation plan, information architecture, storyboard and contents. The second part discussed the challenge in producing the application as intended and outlined several future development approaches. This application attracts users who are looking for service providers and for those looking for a platform to offer their skills, knowledge or any related services. Through this application, users are connected to credible and professional local service providers. Users are also accessed to the best and vocational services like cleaning, plumbing, event catering, interior painting and many more easily. After that, service providers are getting paid to do the work they like or good at using their exceptional skills. In the long term, this application may yield a win-win situation among the users. For example, users can get help when they need any assistance while service providers can earn flexibly on this application. In this project, the developers have learnt how to optimise the application to be more interesting to attract people.